Counseling and Training for Stunting Management Through Provision of Red Kidney Bean Cookies in Kubah Sentang Village Pantai Labu District - Nainggolan, Efendi; Sihotang, Urbanus; Manalu, Mincu (Talenta Publisher Universitas Sumatera Utara, 2022)
Indonesia still has a relatively high stunting prevalence of children under five years. Deli Serdang Regency is one of regencies in North Sumatera Province that has acute-chronic nutritional problems. Provision of additional food in the form of red kidney bean cookies is carried out to overcome nutritional deficiencies that occur in the toddler age group, as well as increase society understanding about stunting, its impact and how to handle it. This community service activity was carried out in Kubah Sentang Village, Pantai Labu District, Deli Serdang Regency, North Sumatra Province. Counseling and training on stunting handling through making red kidney bean cookies was attended by 50 participants consisting of mothers who were members of the PKK group, posyandu cadres, mothers with toddlers, and youth groups. Based on the results of the pre-test and post-test, there was a decrease in the number of participants who had knowledge about stunting in the category less than 41.3% to 13.0%, and as many as 56% of participants had knowledge about stunting in the good category.